Effects of delay on the dynamical behaviour of one-dimensional continuous nonlinear systems - Uçar, A. (Institute of Electrical and Electronics Engineers Inc., 1999)
In this study, the effect of a delay element in a one-dimensional continuous nonlinear system is investigated. It is illustrated that chaotic behavior may occur even in the first order system. The computer generated chaos for the double-scroll attractor and bifurcation diagrams are presented. © 1999 IEEE.
6th IEEE International Conference on Electronics, Circuits and Systems, ICECS 1999 -- 5 September 1999 through 8 September 1999 -- Pafos -- 113616
Keywords: Nonlinear systems; Bifurcation diagram; Chaotic behaviors; Computer generated; Delay elements; Double-scroll attractors; Dynamical behaviours; First order systems; One dimensional